Asuhan Keperawatan Bersihan Jalan Napas Tidak Efektif Pada An. B Dengan Bronkopneumonia di Ruang Firdaus RSI Banjarnegara - Yeni Rahmayani; Murniati M; Etika Dewi C (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The leading cause of illness and mortality in children under five is bronchopneumonia. Child bronchopneumonia is often characterized by tachypnea, cough, decreased appetite, numbness, and nasal breathing. Ineffective breathing is one of clinical signs and issues brought on by inflammatory process of bronchopneumonia, which increases secretion production. Purpose of this study is to provide patients with ineffective respiratory issues with complete nursing care. A case study approach is employed in descriptive research methodology. An.B is subject of case study in this scientific paper. During examination, it was discovered that patient had a cough that was difficult to get rid of, was breathing 26x/minute, ronchi sounds in his left lobe of the lungs, had a blood oxygen saturation 95%, and had pulse rate of 100x/minute. Chest physical therapy and respiratory management are intended interventions. According to case study An.B's outcomes, respiratory issues can be partially resolved following nursing care for three consecutive days by engaging in chest physical therapy. Improvements in effective coughing, sputum production, moderate ronchi voice, frequency of breathing, and anxiety were also noted. Conclusion: Bronchopneumonia in An.B can be partially treated by providing ineffective nursing care that clears breathing channel.